Acoustic characterization of sacred music rendered by a human whistle at the Divine Providence Church in Goa, India - Menino Allan S. M. Peter Tavares (2010)
The human whistle is a representation of the human vocal singing. Singing (solo and congregational) is an essential component of sacred music for collective worship in a Catholic church. The acoustic characterization of sacred music is defined in this paper through a derived Acoustic Comfort Impression Index (ACII) and several Acoustic Worship Indices (AWI), namely, Subjective Sacred Factor (SSaF), Subjective Intelligibility Factor (SInF) and Subjective Si-lence Factor (SSiF). In this study, live sacred music rendered by the human whistle is compared with that by the cello, clarinet, violins and the ensemble, in the Catholic church of the Divine Providence (Goa, India). Among the signifi-cant results, ACII for the human whistle was found to be better than ACII for the musical instruments (F = 2.38, p = 0.08); this difference was more significant at the nave of the church (music source) (F = 2.94, p = 0.04) and lower at the choir loft (music source) (p = 0.21). SInF for the ensemble music was found better than SInF for human whistle (F = 3.07, p = 0.03). At the nave of the church, the SInF was found better than SSaF and SSiF (F = 4.17, p = 0.02). SSaF and SInF were equally better than SSiF at the choir loft (p = 0.02). This study opens the possibility of optimized use of the human whistle in rendering sacred music in a church.